Hierarki Bahasa dalam Tafsir Al-Ibriz li Ma‘rifah Tafsir Al-Qur’an al-‘Aziz Karya K. H. Bisri Musthofa - Ridhoul Wahidi (Lajnah Pentashihan Mushaf Al-Qur'an, 2015)
This paper examines the hierarchy of language in IbrÄ«z li Maâ€™rifah at-TafsÄ«r al-Qurâ€™Än al-â€˜AzÄ«z. The hierarchy of language in the local interpretation of the Qurâ€™an by Musthofa Bisri can be used as a new method in the interpretation of the Qurâ€™an particularly for the local interpretation of the Qurâ€™an of the Archipelago. In this case, there are four levels of language in the hierarchy in the interpretation of Al-Ibriz. The first is called the the Ngoko (rough language). The second is called Madya or regular or intermediate language, the third is called Kromo or polite language, and the the fourth is called Kromo Inggil or the most polite language. The Ngoko, Kromo, and Kromo Inggil are the languages used at the time of dia-logue based on social strata. For example between the the high and the low such as the dialogue between the God (Allah) and the Prophets, the Maria (Maryam) and the angel, the Prophet Isa and his people. At the regular or intermediate level, Bisri Musthofa interprets the verses by using the regular or intermediate language regular language which means that Bisri uses the language that has been widely used by the Javanese people, either in the form of explanation of the verses or the dialogue such as the dialogue of the people of the heaven/paradise and that of the hell.